The effect of an enrichment program in the light of the integrated science, technology, engineering and mathematics (STEM) on developing 21st century skills among Gifted students. - alaaseme, Fahd Mohammed Ghaleb (Universitas Terbuka, 2023)
The study aimed to identify the impact of an enrichment program in the light of STEM integration approach in developing the 21st century skills of Gifted students at the secondary level. The study used a quasi-experimental design, The sample of the study included 60 student from the second year of high school, at Jamal Abdel Nasser High School for Gifted Students, in the capital, Sana'a, and divided into two groups: experimental (30) and control (30)., The researcher built a 21st century skills test, consisting of 46 items, The researcher also built the enrichment program according to the STEM approach, The results showed The enrichment program, in the light of the STEM approach studied by the experimental group, led to the development of the 21st century skills included in the study. The study recommended developing curricula for Gifted students in the light of 21st century skills and using the STEM approach, training teachers on how to use STEM approaches in teaching the gifted, and designing complementary activities and integrating them into the curricula in order to achieve the development of 21st century skills among the Gifted students.